Places of memory in modern China : history, politics, and identity - Matten, Marc Andre (Leiden series in comparative historiography ;, 2012)
The book offers a new approach to the discussion on the issue of Chinese national identity, providing new insights in how identity is constructed and contested. These issues are of vital concern for the understanding of contemporary China and its national consciousness.